Agremiación Colombiana de Trabajo Social - Rodríguez Benavides, Javier Andrés; Guevara Peña, Nora Liliana (Universidad Santiago de Cali, 2025)
This chapter will be of a reflective nature, based on the experience in the relationship with the Association of Social Workers of Valle de Cauca -ATSOVALLE-, and other union construction scenarios at the national level. It is relevant for the organizational process of the association to be part of the triad that configures this research, which made a section where the interactions and dynamics of the previous chapters can be analyzed; an introspection to reveal those elements in the present of the profession, and in turn of the participation in different scenarios of union debate that should contribute to the analysis of working conditions in the profession and the need for organization of the union to dignify the place of the Social Work in Colombia. The chapter identifies recent milestones, the consolidation of the Social Work union in the Valle del Cauca region, establishes a relationship between the importance of joining unions, generational changes, and approaches to some problematizations and professional challenges of a political-academic nature in the Sciences. Social, in terms of fields of action, research, better working conditions and the defense of the profession that leads it to recover and strengthen its place of incidence in public and social policies as an opportunity within the framework of the proclaimed progressive government, initiated in 2022 by the presidency of Gustavo Petro Urrego and Vice President Francia Elena Márquez Mina.